Custom, Land and Livelihood in Rural South China : The Traditional Land Law of Hong Kong's New Territories, 1750-1950 - Hase, P. H. (Royal Asiatic Society Hong Kong studies series., 2013)
Land was always at the center of life in Hong Kong's rural New Territories: it sustained livelihoods and lineages and, for some, was a route to power. During imperial times villagers managed their land according to customs that were often at odds with formal Chinese law. British rule, 1898 to 1997, added complications by assimilating traditional practices into a western legal system. Custom, Land and Livelihood in Rural South China explores land ownership in the New Territories, analyzing over a hundred surviving land deeds from the late Qing Dynasty to recent times, which are transcribed in full and translated into English. Together with other sources collected by the author during thirty years of research, these deeds yield information on all aspects of traditional village life -- from raising families and making a living to coping with intruders -- and evoke a view of the world which, despite decades of urbanization, still has resonance today.